2020
DOI: 10.5812/hepatmon.101722
|View full text |Cite
|
Sign up to set email alerts
|

Occult Hepatitis B Virus Infection Prevalence Among Different Populations of Iran: A Systematic Review and Meta-Analysis

Abstract: Context: Various frequency rates of occult hepatitis B virus infection (OBI) are reported from different parts of Iran. This systematic review and meta-analysis aimed to characterize the OBI epidemiology in Iran and estimate the pooled prevalence among different populations. Evidence Acquisition: Nine international and Persian electronic databases, as well as some conference proceedings, were searched. Original cross-sectional studies up to December 2018 were included if they investigated the prevalence of OBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 54 publications
(25 reference statements)
1
16
1
Order By: Relevance
“…Viral DNA was detected in 30% of high-risk people in Iran [15] . In a systematic and meta-analysis study in Iran, the prevalence of OBI was 0.06% among blood donors regardless of anti-HBc result and 7.90% among anti-HBc-positive donors [13] . In the present study, among 31 anti-HBc-positive and HBsAg-negative samples (suspected OBI), only one (3.22%) sample was positive for HBV DNA (confirmed seropositive OBI).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Viral DNA was detected in 30% of high-risk people in Iran [15] . In a systematic and meta-analysis study in Iran, the prevalence of OBI was 0.06% among blood donors regardless of anti-HBc result and 7.90% among anti-HBc-positive donors [13] . In the present study, among 31 anti-HBc-positive and HBsAg-negative samples (suspected OBI), only one (3.22%) sample was positive for HBV DNA (confirmed seropositive OBI).…”
Section: Discussionmentioning
confidence: 98%
“…A systematic review and meta-analysis showed the high occurrence of OBI among Iranian high-risk people. Prevalence of OBI was variable in different regions of Iran, from zero to 63.1% in the HIV-positive people in Fars province [13] . However, knowledge about the prevalence of HBV among HIV-infected people in Iran is less, especially in the Kurdistan province.…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, approximately 2-3% of people are carriers of the virus, and nearly 300,000 people are suffering from hepatitis, cirrhosis, or hepatocellular carcinoma. In Iran, 70-80% of chronic hepatitis results from HBV as the primary cause (2,(9)(10)(11).…”
Section: Importance Of Vaccination In Dhcpmentioning
confidence: 99%
“…These patients might be positive or negative for the serological markers of previous infection. [1][2][3] Occult HBV infection usually occurs after acute self-limited or chronic hepatitis B in which HBsAg is absent or undetectable due to suppression of viral replication and HBsAg expression under the host immune responses or mutations in the S region of the genome and the production of the modified HBsAg that is unrecognizable by routinely used HBsAg detection assays. 4 In addition to the host and viral factors, hepatitis C virus (HCV) coinfection might have a role in the development of occult HBV infection through inhibition of HBV replication and HBsAg expression.…”
Section: Introductionmentioning
confidence: 99%